1986
DOI: 10.1111/j.1755-3768.1986.tb06863.x
|View full text |Cite
|
Sign up to set email alerts
|

Human retinal pigment epithelium in long term explant culture

Abstract: Explants of human retinal pigment epithelium were maintained in culture in various types of media, and examined by light and transmission electron microscopy. After one month in vitro, the central areas showed a monolayered configuration with distinct polarity and presence of ruthenium red stainable material on the apical surface. On the peripheral areas of Bruch's membrane, multilayered lesions were observed to develop and to extend from the monolayered epithelium and past the cut edge in Bruch's membrane. Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…I n the present study, pigment cells outside the lesion area retained several of the in vivo characteristics. l'his is in concordance with a previous organ culture study where Ham's F10 medium was demonstrated to support maintenance of' the epithelium in long-term culture (Nicolaissen J r et al 1986). It further indicates that the alterations observed in the lesion area are not effectuated by a modulating activity of the medium per se.…”
Section: Fzgsupporting
confidence: 90%
See 1 more Smart Citation
“…I n the present study, pigment cells outside the lesion area retained several of the in vivo characteristics. l'his is in concordance with a previous organ culture study where Ham's F10 medium was demonstrated to support maintenance of' the epithelium in long-term culture (Nicolaissen J r et al 1986). It further indicates that the alterations observed in the lesion area are not effectuated by a modulating activity of the medium per se.…”
Section: Fzgsupporting
confidence: 90%
“…This finding confirms the stable character of the monolayered organization of the pigment epithelium. It is retained in vitro under a multitude of culture conditions on plastics (Hayashi et al 1978;Flood et al 1980;Basu et al 1983), collagen (Hall & Quon 1981), on Bruch's membrane (Tso et al 1973;Nicolaissen J r et al 1986), and on vitreous gels (Forrester et al 1986).…”
Section: Fzgmentioning
confidence: 99%